ภาวะสุขภาพและปัจจัยที่เกี่ยวข้องกับสุขภาพของบุคลากรโรงพยาบาลเซนต์หลุยส์ในปี พ.ศ. 2546 - อรวรรณ น้อยวัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
Background : The health promotion of hospital personnel is the first active activity of health promotion hospital. The importance of physical and mental health status will lead to the development and linking with community and health promotion hospital. Objective : To investigate health status and related factors of personnel at Saint Louis Hospital. 2003. Research Design : Cross-Sectional Descriptive Study Participants : The personnel in Saint Louis Hospital ,2003 Data Collection : The Self-administered questionnaire was conducted during January-February 2004 with 820 personnel (88.1%) Statistical Method: Chi-square test ({u1D4B3}2) Result : The result of this study showed that 820 health personnel checkup were male : female 1 : 4.5 1 mean age was 33.8 years .mostly in age group 30-34 years (26.6%) , Most of them were Buddhist 44.2% and Christian 23.5%. It was found that the mean score knowledge health behaviors was moderate 58.1% , attitudes at good scores level 74.7% , good health behaviors 79.9% , moderate stress level 39.4% and high stress level 38.0%. The physical and laboratory examination results showed that body mass index abnormal (<20 and >25) 46.7% , abnormal Blood Pressure (Systolic/Diastolic > 140/90) 12.3 % and abnormal Chest X-Ray 1%. The personnel over 35 years of age showed abnormal Fasting Blood Sugar (>110 mg%) 7.3% and abnormal Cholesterol (>200 mg%) 48.8%. It was also found that the physical health status was statistically associated with age , position of work , quantity of work and sleeping behavior (p < 0.05) Conclusion : The health status and related factors of hospital personnel is very important for the baseline data in development of health status of personnel at Saint Louis hospital.